2021
DOI: 10.3390/medicina57030295
|View full text |Cite
|
Sign up to set email alerts
|

QT Interval Prolongation in Patients with Systemic Sclerosis—Are the Holter ECG Recordings a Better Option for QT Interval Evaluation?

Abstract: Background and Objectives: Cardiac involvement in systemic sclerosis has important consequences on patient survival. Myocardial fibrosis and microcirculation involvement can generate arrhythmic complications, which can be associated with a higher death risk. QT interval prolongation is considered as a risk factor for ectopic ventricular events and can be evaluated using standard short ECG recordings or 24-h Holter ECG recordings. Materials and Methods: 39 patients with systemic sclerosis were submitted to a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…These results are similar to other studies [9,20,24] confirming the link between inflammatory process and QTc interval prolongation. Only the number of the sinusal QRS with QTc > 450 ms recorded during 24 h monitoring was significantly correlated with the number of premature ventricular contractions (PVC), a correlation confirmed also in patients with systemic sclerosis [29]. In our study, the percentage of RA patients (54%) with ventricular arrhythmic events was similar to the results of previous studies that used 24 h Holter monitoring, studies which were not able to identify any significant differences between patients with RA and controls with respect to these events [30,31].…”
Section: Discussionmentioning
confidence: 70%
“…These results are similar to other studies [9,20,24] confirming the link between inflammatory process and QTc interval prolongation. Only the number of the sinusal QRS with QTc > 450 ms recorded during 24 h monitoring was significantly correlated with the number of premature ventricular contractions (PVC), a correlation confirmed also in patients with systemic sclerosis [29]. In our study, the percentage of RA patients (54%) with ventricular arrhythmic events was similar to the results of previous studies that used 24 h Holter monitoring, studies which were not able to identify any significant differences between patients with RA and controls with respect to these events [30,31].…”
Section: Discussionmentioning
confidence: 70%
“…If any conflicts emerged during the review process, they were resolved by discussion among the readers. Sixty articles were finally included in this systematic literature review [ 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ...…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of premature ventricular contractions (PVC) ranged from 3.7% (1/27) to 100% (39/39) in a SSc cohort with prolonged QT, for which the number of PVC on the Holter EKG was significantly higher ( p = 0.04) in patients with dcSSc compared to lcSSc [ 15 , 59 ]. Of the studies that reported mean PVC, this value varied between 197 ± 527 and 2046.1 ± 6027.8 [ 21 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent ECG abnormalities in SSc patients are represented by P wave abnormalities, non-specific abnormalities of ST-segment and T wave, QRS micro voltage, and more subtle changes like the low values of the heart rate variability parameters, QT dispersion (QTd) increase. 9 The prolongation of QTc interval has been also observed in patients with SSc without cardiac manifestations and in the absence of echocardiographic abnormalities which can lead to life threatening tachyarrhythmias. 10 …”
Section: Introductionmentioning
confidence: 99%